2013
DOI: 10.1227/neu.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neurological Deterioration After Mild Head Injury

Abstract: The incidence of delayed neurological deterioration after MHI with ICH is low and usually occurs within 24 hours after admission. It results in significant morbidity and mortality if it is the result of progressive intracranial hemorrhage. Further research is needed to identify risk factors that can allow early detection and improve outcomes in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Intracranial bleed complicates initial evaluation of mild head injury since a small percentage of patients with intracranial hemorrhage remain neurologically stable during clinical evaluation but then deteriorate within 24 hours of injury. 12 , 13 We suspect that the significant rate of return ED visits associated with bleed on head CT is driven by two factors. First, neurological symptoms do not appear immediately with intracranial hemorrhage, so patients may be discharged before clinical assessment can identify anything of medical concern.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial bleed complicates initial evaluation of mild head injury since a small percentage of patients with intracranial hemorrhage remain neurologically stable during clinical evaluation but then deteriorate within 24 hours of injury. 12 , 13 We suspect that the significant rate of return ED visits associated with bleed on head CT is driven by two factors. First, neurological symptoms do not appear immediately with intracranial hemorrhage, so patients may be discharged before clinical assessment can identify anything of medical concern.…”
Section: Discussionmentioning
confidence: 99%
“…Other excluding factors, given evidence suggestive of higher risk, included GCS <15, epidural hemorrhage (EDH), anticoagulation or coagulopathy, hemodynamic instability, and additional systemic injuries. 2,21,22 Aspirin usage was not considered a high-risk feature. 22 Although subdural hematomas were excluded from our initial protocol, subsequent studies have suggested that some subdural hematomas in the setting of mTBI are at low risk of progression.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, brain atrophy and coagulopathy are the risk factors associated with haematoma formation and progression after head injury. 5–9 Coagulation disorder and brain atrophy accompanied by anorexia nervosa are considered the primary causes underlying the formation of acute subdural haematoma in young woman despite minor head injury. But few intracranial haemorrhages have been reported as a complication of anorexia nervosa.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with anorexia nervosa can easily experience falls because of decreased muscle strength, syncope and hypoglycaemic faints, which lead to complications such as intracranial haemorrhage and haematoma enlargement because of brain atrophy, coagulation disturbances and vascular fragility. 4 6 Treatment is inaccessible in numerous cases of anorexia nervosa. 11 The age of patients with eating disorders is advancing 18 ; the number of traumatic intracranial haemorrhage with minor head trauma is expected to increase in future.…”
Section: Discussionmentioning
confidence: 99%